Bevacizumab in temozolomide refractory high-grade gliomas: single-centre experience and review of the literature. (19th January 2018) - Jeck, Jennifer; Kassubek, Rebecca; Coburger, Jan; Edenhofer, Simone; Schönsteiner, Stefan S.; Ludolph, Albert C.; Schmitz, Bernd; Engelke, Jens; Mayer-Steinacker, Regine; Lewerenz, Jan; Bullinger, Lars
Background: Despite multidisciplinary treatment approaches, the prognosis for patients with high-grade glioma (HGG) is poor, with a median overall survival (OS) of 14.6 months for glioblastoma multiforme (GB). As high levels of vascular endothelial growth factor A (VEGF) are found in HGG, targeted anti-antiangiogenic therapy using the humanized monoclonal antibody bevacizumab (BEV) was studied in a series of clinical trials. Still, the discrepancy of BEV's efficacy with regard to initial clinical and radiological response and its reported failure to prolong survival remains to be explained. Here, we illustrate the effectiveness of BEV in recurrent HGG by summarizing our single-centre experience. Methods: We have retrospectively investigated the effect of BEV in temozolomide refractory HGG in 39 patients treated at the University Hospital of Ulm, Germany. Results: Median duration of BEV treatment was 12.5 weeks; 23% of patients received BEV for more than 6 months and 15% for more than 1 year, until clinical or radiological tumour progression led to discontinuation. Furthermore, Karnofsky performance status increased in 30.6% and steroid dose decreased in 39% of all patients. Conclusions: The review of literature reveals that phase II and III studies support BEV as an effective therapy in recurrent HGG, at least with regard to progression-free survival (PFS), but landmark phase III trials failed to prove benefit concerning OS. Here, we discuss reasons that may account for this observation. We conclude that prolonging PFS with maintenance of neurological function and personal and economic independency justifies the off-label use of BEV.